Entrepreneur and employee negotiated labour market flexibility in small firms. (3rd July 2022) - Murthy, Venkatesh; G, Jaganth; Paul, Bino
ABSTRACT: We investigated negotiated Labour Market Flexibility (LMF) in small hazardous firms in the context of increased immigrant labourers and the non-availability of the local labour force. Extant literature discussed negotiation between the employer and employees, only if the firm satisfies the following conditions: firm-specificity, employee categorisation into core-periphery, and shared ethnic identities between the employees and employer. However, in this study, we broke away from these conditional boundaries, and used the Grounded theory to capture both entrepreneurs' and employees' views. Interestingly, we found a socially constructed interdependence between them, stemming from mutual reciprocity. The findings offer significant implications for substantive theory and practice in the realm of LMF in general, and negotiated flexible work arrangements in particular.